Strong and weak links: Talent distribution within teams - Novet, A. (Hockey Graphs, 2017)
In the salary cap world, hockey is a game of resource allocation. Each team is given a set amount of money to acquire players. Consequently, hockey inevitably becomes about tradeoffs. When building a team, every dollar spent on one player is a dollar that can`t be used for another. There are certainly times when you can get a bargain, but you will always have to make decisions about spending priorities.